2012
DOI: 10.1097/jto.0b013e3182598a91
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Prognosis of Recurrent Thymoma Management

Abstract: World Health Organization histologic types AB or B1 and complete re-resection are favorable prognostic factors of recurrent thymoma. In particular, complete re-resection of recurrent thymoma contributes to better survival than other management. Therefore, we suggest that long-term surveillance extended at least 20 years may be essential for early detection of recurrence to increase the chance of complete re-resection of recurrent thymoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 23 publications
9
52
3
Order By: Relevance
“…Thus, reoperation may be recommended for recurrent thymoma whenever complete resection is possible. However, the rate of complete resection was low in previous studies (50% to 90%) [4,[6][7][8]16,17,24], which is consistent with our data. And we found that single recurrence had higher complete resection rate than multiple recurrence.…”
Section: The Outcomes Of Recurrent Thymomasupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, reoperation may be recommended for recurrent thymoma whenever complete resection is possible. However, the rate of complete resection was low in previous studies (50% to 90%) [4,[6][7][8]16,17,24], which is consistent with our data. And we found that single recurrence had higher complete resection rate than multiple recurrence.…”
Section: The Outcomes Of Recurrent Thymomasupporting
confidence: 83%
“…Whereas, unlike the previous studies [3,4,[6][7][8]12,[16][17][18][19][20][21], we observed that much high percent (71.4%) of patients who underwent reoperation received adjuvant chemotherapy, radiotherapy, or chemoradiotherapy, which may improve the treatment outcomes of recurrent thymoma and confound the benefit of reoperation. Based on that adjuvant treatment can improve the outcomes of patients who have median survival interval after recurrence of the chemotherapy group was higher compared with the group of patients without retreatment, but no statistical significance (P=0.062).…”
Section: The Outcomes Of Recurrent Thymomacontrasting
confidence: 53%
See 2 more Smart Citations
“…The risk of cardiac toxicity is even more increased because of previous use of mediastinal radiotherapy and the potential development of paraneoplastic myocarditis [101]; the use of less toxic agents, including paclitaxel [97] or pemetrexed [92]. In case of recurrence, the strategy may actually primarily consist of a similar multimodal management to that conducted at time of first diagnosis, with surgery and radiotherapy in eligible cases [102][103][104][105]. Complete resection remains a major prognostic factor in this setting.…”
Section: Palliative-intent Definite Chemotherapymentioning
confidence: 99%